The relationship between hypertension and angina pectoris; physiological & Biochemical study of patients Samarra city - Mostafa A. Abdulrahman (Tikrit Journal of Pure Science)
This study was conducted for the period from 09/2013 to 02/2014 at Samarra General Hospital labs with patients admitted in the corridors of recovery for the patients with angina pectoris; ratio to the disease of hypertension is the pressure measurement during a hospital, (50-65) age nonsmoker. Reveiew as results  showed high significant in hypertension for people in hypertension , angina pectoris compared with the control group in,as well as high significant in lipid profile (cholesterol, triglycerides). the high increase in angina pectoris group compared hypertension with group compared with control group at the level( P <0.05 ). As for the lipoproteins, a decrease significant in the concentration of HDL-C was the largest decrease  in angina pectoris when compared with hypertension  group and the control group. at the same time high LDL-C concentration in a angina pectoris when compared with the control group, as to the biochemical variety results for increase significant in the concentration of blood sugar in the two study groups .show results high in angina pectoris when compared with hypertension group and the control group ,uric acid show results high in angina pectoris when compared with hypertension group and the control group.